Validation Study of MaxSignal® Histamine Enzymatic Assay for the Detection of Histamine in Fish/Seafood. (23rd November 2019) - Gone, Swapna; Kosa, Nicolas; Krebs, Joseph; Hungerford, James; Trucksess, Mary; DeWitt, Christina
Abstract: Bioo Scientific Corp. has developed a rapid enzymatic quantitative assay for the determination of histamine in seafood. Fresh/frozen tuna, canned tuna, pouched tuna, and frozen mahi mahi samples were used for the validation study under the specific guidelines of the AOAC Research Institute Performance Tested Methods SM program. Recoveries ranged from 82 to 107% at concentrations ranging from 6 to 72 ppm, with RSDr values between 0.8 and 6.5% (6–72 ppm). The linearity of the assay ranged from 0 to 108 ppm, with R 2 values exceeding 0.99. The LOD was 0.9 ppm and the LOQ was 2.6 ppm for frozen tuna, which gave the lowest background level of contaminant. Cross-reactivity of the assay was tested against 14 other biogenic amines and was found to be minimal for all (<0.5%), except for agmatine (4.1%) and putrescine (0.9%). There was no observable interference from any tested biogenic amines. Product consistency was verified by validating lot-to-lot variations and variations within the same lot. Overall recoveries for all tested matrixes were within the acceptable range (80–120%). A 1-year claimed shelf life of the kit at 4°C was verified by accelerated stability study data collected on days 1, 15, and 32 at 25°C and by real-time stability testing at 1-month, 6-month, and 1-year at 4°C. No difference in histamine detection was observed in ruggedness testing, in which minor changes were introduced to the assay protocol. Good agreement was observed between AOAC Official Method SM 977.13 and the MaxSignal ® Histamine Enzymatic Assay method. Independent laboratory testing demonstrated that the MaxSignal method works with the same precision in the hands of minimally trained technicians as with the expert method developers. This study validates the performance of Bioo Scientific's rapid enzymatic method.